2008
DOI: 10.1007/s00266-008-9128-8
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermis-Assisted Breast Reconstruction

Abstract: Acellular dermis appears to be a useful adjunct in immediate prosthetic breast reconstruction. Acellular dermis-assisted breast reconstruction has a low complication rate, helps to reconstruct an aesthetically pleasing breast, and facilitates expeditious completion of the reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
218
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(242 citation statements)
references
References 12 publications
8
218
2
8
Order By: Relevance
“…For example, Spear et al reported a 45.5% complication rate in irradiated breasts compared to 4.3% in nonirradiated breasts reconstructed with AlloDerm ® [2]. In the present study, it is noticeable that the frequency of implant/ TE losses was higher in irradiated Surgisis ® patients than in non-irradiated Surgisis ® patients (40% vs. 11%).…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…For example, Spear et al reported a 45.5% complication rate in irradiated breasts compared to 4.3% in nonirradiated breasts reconstructed with AlloDerm ® [2]. In the present study, it is noticeable that the frequency of implant/ TE losses was higher in irradiated Surgisis ® patients than in non-irradiated Surgisis ® patients (40% vs. 11%).…”
Section: Discussionsupporting
confidence: 44%
“…Often stated advantages [1] with the use of matrix are a better aesthetic result, with a better control and definition of the implant pocket and inframammary fold, and the possibility to use a dual-plane technique and less muscle dissection [2][3][4]. However, it is difficult to evaluate the aesthetic result after breast reconstruction, as there are no validated instruments available and no consensus on how the evaluation should be performed [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of them still involve implant-based procedures. This is due to the fact that implant-based reconstruction is a less invasive option when compared to autologous approaches as there is generally a decrease in morbidity but also it being the most costeffective method (1)(2)(3). Current available literature shows that implant-based reconstruction is used in 37% of breast cancer patients (4,5).…”
Section: Complications Requiring Revision Surgery Did Not Differ Signmentioning
confidence: 99%